From Individual to Collective Thuggrery in Coastal Environment Semarang (from Dutch Colonial Period to Post Independence Revolution) - Sri Hartatik Endah (EDP Sciences, 2021)
Semarang is one of the Dutch colonialisem and capitalist center from the 19th century to 19th the mid-20th centuries. This economic environment created a financial gap between the indigenous people and the foreign ones. Hence, crime emerged as a result of the hole. This study analyzes the criminal pattern that occurred in Semarang from the colonial period to the post-independence revolution—collecting and analyzing data using the historical method by four stages, namely heuristic, critics, interpretation, and historiography. The sources were from contemporary newspapers. The results show that there is a different criminal pattern from the colonial era to post-independence. Crime in the colonial period was individual-based. The crime scenes were on roads and markets, and the targets were the rich people regardless of ethnicity and nationality. On the other hand, criminal patterns in the post-independence era carried out in groups by robbing the houses owned by foreign people, such as Europeans or Chinese. Thus, the study concludes that the situation during the period influences the criminal pattern. The economy is the factor that triggered the crime during the colonial era. However, the anti-foreign movement caused crime activities during the post-independence period.